Patient-Specific Instrumentation vs Standard Referencing in Total Ankle Arthroplasty: A Comparison of the Radiologic Outcome. (June 2022) - Heisler, Lukas; Vach, Werner; Katz, Georg; Egelhof, Thomas; Knupp, Markus
Background: Existing literature on the superiority of patient-specific instrumentation (PSI) in total ankle arthroplasty (TAA) over standard referencing (SR) is limited. Advantages presented include better implant alignment, shorter operating times, and increased accuracy of implant size prediction. The aim of this retrospective study was to analyze PSI in the hands of an experienced foot and ankle surgeon new to both PSI and SR for this specific implant, in regard to determining implant alignment, operative times, and radiologic short-term outcome and predicting implant size for tibial and talar components. Methods: Twenty-four patients undergoing TAA using PSI were compared to 25 patients using SR instrumentation. Outcome measures included alignment of the tibial component (α coronal plane, γ sagittal plane), the tibiotalar tilt (β), and the talar offset x on the sagittal view as well as the presence of radiolucent lines, operation time, and wound healing. Postoperative outcome was assessed at 6 weeks, 4 months, and 1 year postoperatively. Results: Implant positioning was similar in both groups, and no advantage in regard to the operative time could be seen when comparing TAA using PSI to SR. Implant size prediction was more reliable for the tibia than for the talus. Three patients (1 from the SR group and 2 from the PSI group) showed radiolucent lines around the tibial component. Two patients (both SR group) suffered delayed wound healing, albeit not requiring any additional measures. Conclusion: The PSI method did not show an advantage over SR in regard to positioning of the components or the duration of the surgery. The current study suggests that no initial advantage of PSI over SR are to be expected in standard total ankle replacement. Level of Evidence: Level III, retrospective study.